PROFILE OF ANIMAL BITE CASES ATTENDING RURAL HEALTH CENTRE IN KANCEEPURAM DISTRICT, TAMILNADU. - DR. P. MOHANKUMAR; DR. C. SIVAGURUNATHAN; DR.R. UMADEVI (International Journal of Pharma and Bio Sciences, 2015)
Rabies is an acute and fatal viral encephalitis transmitted from infected animal to humans. It is 100% fatal disease, but with timely,appropriate treatment, it is 100% preventable. There is a lot of misconceptions regarding rabies, due to inadequate knowledge regarding rabies, some of the animal bite victims ignores timely management. It is important to know about the practice in the community, and factors influencing post exposure treatment and to initiate measures against the wrong practices. To study the practices followed by the animal bite victims following exposure and to find out the misconception regarding animal bite among victims. Proportions. Out of total 140 cases of animal bite, 47.2% were below 25 years of age. Majority of the animal bite victims was in the age group of 5 to 15 years. Majority of bites were due to stray dogs (92.8%). Only 15% of animal bite victims washed their wound with soap and water after the bite. Majority of the animal bite victims did not do appropriate wound management warrantsa great deal of information through health education with the community.